A STUDY OF THE EFFECTIVENESS OF DISTANCE LEARNING AT A MEDICAL UNIVERSITY IN UKRAINE - H.Yu. Morokhovets; Yu.V. Lysanets; O.M. Bieliaieva; S.A. Stetsenko; O.A. Shlykova (Проблеми екології та медицини)
This paper analyzes the experience of introduction of distance learning in Ukraine, explores the efficiency of online learning in comparison with the classroom form of education, and identifies the role of motivation in the process of distance learning and the factors influencing the effectiveness of online learning. The aim of this research is to determine, theoretically substantiate and experimentally test the effectiveness of distance learning at a medical university. The authors analyzed the results of a survey of 315 medical and dental students of Poltava State Medical University at the second (Master's) and third (PhD) levels of higher education. Our research relies on the assertion that online learning influences not only the level of students’ motivation to continue their studies, but also the attitude toward their future profession. Therefore, upon receiving online training, students’ learning motives and perception of the attractiveness of the profession were used to measure the effectiveness of online mode of education. Distance learning aims to individualize the process of acquiring knowledge remotely using modern information and communication technologies. At the same time, it is necessary to monitor the learning outcomes and examine their dependence on the growing popularity of online learning in the world. We developed a questionnaire based on Donald Kirkpatrick’s model and applied the method of studying the attractiveness factors of the profession. 85.49% of respondents demonstrated their general impression of the organization of distance learning as positive (271 respondents). 74.13% of respondents were satisfied with the organization of distance learning at the university. To the question “How clearly do you understand how to apply the knowledge acquired through distance learning?” according to the scale from 1 to 5 (1 – not clear at all, 5 – very clear) respondents distributed their votes as follows – 1.58%, 7.26%, 29.97%, 43.53% and 17.66% respectively. The results of the survey on this issue correlate with the results of the test control conducted within the survey (r = 0.31). Experimental testing showed differences between the general impression of the organization of distance learning among students and the level of knowledge they acquired during distance learning. The level at which students determined the complexity of work during distance learning did not correlate with the results of test control of respondents (r=-0.04745, р=0.4028), and the age of respondents (r=0.1379, р=0.0242). The level of technical skills in working with software and web resources depended on the age of respondents (r=0.2432, р<0.0001) and did not correlate with the level at which students determined the complexity of work during distance learning (r=0.0818, р=0.1826), and the level general impression of studying the discipline (r=-0.0972, р=0.1130). The presence of previous experience of distance learning did not correlate with the performance in the discipline (r=0.003982, р=0.9441), which indicates that previous experience of distance learning does not affect the effectiveness of this mode of training in general. The results of the survey allow us to state that the effectiveness of distance learning is not affected by sex and level of education. Instead, there is reason to believe that communication and technical skills can have a significant impact on the efficiency of this process. The theoretical and methodological aspects of foreign experience in the use of special software (learning management systems, databases, software shells) require further research to optimize the process of distance learning.